2008
DOI: 10.1159/000132567
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Antibodies in Breast Cancer HER2 Diagnostics

Abstract: Overexpression and/or gene amplification of the HER2 oncogene predicts worse prognosis and altered sensitivity to chemotherapy. Trastuzumab is capable of improving prognosis of HER2-positive breast cancer, but for the success of treatment appropriate HER2 testing is essential. Our aim was to determine the value of immunohistochemical (IHC) screening prior to fluorescence in situ hybridization (FISH). We assessed five conventional IHC assays (NCL-CB11, Pathway CB11, CBE356, CBE1, HercepTest) and the novel rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…These suboptimal conditions probably resulted in a decreased sensitivity of 4B5, and may have contributed to the lower number of level 2+ cases. However, 4B5, under the conditions tested, showed substantial overall accuracy, with a higher specificity and positive predictive value than FISH . Staining results with 4B5 have been highly comparable with those of P‐CB11: the difference between P‐CB11 and 4B5 involves 4B5 scoring fewer level 2+ cases, thus yielding a higher concordance with FISH .…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…These suboptimal conditions probably resulted in a decreased sensitivity of 4B5, and may have contributed to the lower number of level 2+ cases. However, 4B5, under the conditions tested, showed substantial overall accuracy, with a higher specificity and positive predictive value than FISH . Staining results with 4B5 have been highly comparable with those of P‐CB11: the difference between P‐CB11 and 4B5 involves 4B5 scoring fewer level 2+ cases, thus yielding a higher concordance with FISH .…”
Section: Discussionmentioning
confidence: 78%
“…These results further support 4B5 as a clinically relevant assay for HER2 expression in breast carcinoma. Studies comparing 4B5 and FISH results in breast cohorts have demonstrated that 4B5 has a higher concordance with FISH than other pharmacodiagnostic HER2 antibodies . In one comparison of 4B5 with HercepTest, the results for 4B5, used according to the manufacturer's protocol, differed little from those reported for HercepTest (correlation P < 0.005) .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations